Heterogeneity in signaled active avoidance learning: substantive and methodological relevance of diversity in instrumental defensive responses to threat cues - Galatzer-Levy, Isaac R.; Moscarello, Justin; Blessing, Esther M.; Klein, JoAnna; Cain, Christopher K.; LeDoux, Joseph E. (Frontiers in Systems Neuroscience, 2014)
Individuals exposed to traumatic stressors follow divergent patterns including resilience and chronic stress. However, researchers utilizing animal models that examine threat responses typically use central tendency statistics that assume population homogeneity, potentially overlooking fundamental differences that can explain human diversity in response to traumatic stressors. The current study tests this assumption by identifying and replicating common heterogeneous patterns of response to signaled active avoidance (AA) training where rats are trained to prevent an aversive outcome (shock) by performing a instrumental behavior (shuttling between chambers) during the presentation of a conditioned threat cue (tone). Study 1 conducted three days of signaled AA training (n = 81 animals) and study 2 conducted five days of training (n = 186 animals). Four trajectories were identified in both samples including animals that acquired and retained avoidance behavior on the first day (Rapid Avoiders: 22% & 25%); those who never successfully acquired avoidance (Non-Avoiders; 20% &16%); a modal class who acquired avoidance over three days (Modal Avoiders; 37% & 50%); and a population who demonstrated a slow pattern of avoidance, failed to fully acquire avoidance in study 1 and did acquire avoidance on days 4 and 5 in study 2 (Slow Avoiders; 22.0% & 9%). With the exception of the Slow Avoiders in Study 1, populations that acquired demonstrated rapid step-like increases leading to asymptotic levels of avoidance. These findings indicate that avoidance responses are heterogeneous in a way that may be informative for understanding resilience and chronic stress responses such as PTSD as well as the nature of instrumental behavior acquisition. Characterizing heterogeneous populations based on their response to threat cues would increase the accuracy and translatability of such models and potentially lead to new discoveries that explain diversity in instrumental defensive responses.